2003
DOI: 10.1016/s0003-4975(03)00831-2
|View full text |Cite
|
Sign up to set email alerts
|

Thymic carcinoma: involvement of great vessels indicates poor prognosis

Abstract: Background. Thymic carcinoma is a rare, indolent, and invasive cancer. This study investigated the treatment results of thymic carcinoma and clinical prognostic factors.Methods. From June 1988 to January 2002, 38 patients were enrolled in this study with the diagnosis of thymic carcinoma in the Cheng-Kung University Hospital based on Rosai's and Muller-Hermelink's classification. Clinical and pathologic data were retrospectively reviewed. Survival analysis was performed using the KaplanMeier, log rank, and Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 18 publications
12
73
2
2
Order By: Relevance
“…It is noteworthy that we could detect a mediastinal liposarcoma, which is known as a disease with a poor prognosis 22) at the early stage and this led to surgical resection. On the contrary, chest radiography did not contribute to the early detection of malignant tumors in the present study despite resectability being the important prognostic factor in thoracic malignancies [23][24][25][26] . It is known that mediastinal tumors occur less frequently than lung tumors, and more than 80% of these tumors are benign histologic types 23,27) .…”
Section: Discussioncontrasting
confidence: 81%
“…It is noteworthy that we could detect a mediastinal liposarcoma, which is known as a disease with a poor prognosis 22) at the early stage and this led to surgical resection. On the contrary, chest radiography did not contribute to the early detection of malignant tumors in the present study despite resectability being the important prognostic factor in thoracic malignancies [23][24][25][26] . It is known that mediastinal tumors occur less frequently than lung tumors, and more than 80% of these tumors are benign histologic types 23,27) .…”
Section: Discussioncontrasting
confidence: 81%
“…Some authors have reported that incomplete surgical resection did not negatively impact long-term survival in cases that received postoperative cisplatin-based therapy [11], whereas other have noted that total resection of a thymic carcinoma significantly increased survival rate [12][13][14]. The present analysis also demonstrated that patients who received total resection had better prognosis.…”
Section: Commentssupporting
confidence: 52%
“…It was a large tumor in the anterior mediastinum that pleura, lung, left brachiocephalic vein, or regional lymph nodes. 7 Chest CT and MRI fi ndings are useful for differentiating thymoma from thymic cancer. The presence of irregular contour, necrosis, a cystic component, heterogeneous enhancement, lymphadenopathy, and/or great vessel invasion on CT or MRI are strongly suggestive of thymic cancer.…”
Section: Discussionmentioning
confidence: 99%